(untitled) (Biological Sciences - PJSIR, 2000)
Experiments have been conducted in an externally cooled batch chiller (crystallizer) to study the effects of (i) agitation level, (ii) stirrer design and (iii) quality of sea bittern, on the recovery of magnesium sulphate and other variables like heat flow rate, heatof crystallization and heat transfer coefficient. The studies indicate that the linearity of temp-time plot and its slope are neither affected by the agitation level nor by quality of sea bittern (excepting spent sea bittern). Recovery/crystallization patterns (or cone-temp relationships) have been found critically dependent on agitation level, degree of turbulence, stirrer design and bittern quality. Three straight blades stirrer is found to be more suitable whereas, 6 curved blades stirrer causes greater turbulence thereby resulting into reduced recovery. The optimum level of agitation is found to be around 165 r p m (tip velocity 62.5 m rnin’ and Reynolds number 13000), around which incidently, both, (a) percent recovery against temperature and (b) energy consumed in stirring, Kj rnin’ Vs Reynolds number behave linearly, the recovery is at its optimal, and the energy consumption is minimum. Beyond the optimallimitof(165 rm p) 62.54 m min’ tip velocity, thepcrform- ance parameters become independent of agitation rate, however, under such situation they are influenced by the quality of sea bittern and hence found to change unpredictably. Normal sea bittern is found to be asuitable raw material, whereas any pretreatment of normal bittern renders it unsuitable and at times an uneconomical raw material.